IMPLEMENTASI KEBIJAKAN PERIZINAN DAN PEMBERITAHUAN KEGIATAN MASYARAKAT PADA KEPOLISIAN RESORT (POLRES) KOTA KENDARI - Mutiasari Mutiasari; Muh Nur Yamin; Syamsul Alam (Pascasarjana Universitas Halu Oleo, 2016)
This studywas conducted todetermine and analyze the implementation ofthe licensing policies and notices of community activitiesin Kendari City Police and kornunikasi factors, resources ,disposition, and structure influence the implementation ofthe licensing policies and noticesof community activitiesin Police Kendari. The results showed that the licensing policies and notices masyatakat activitie simple mentedby(a) Providea receiptnotice(b) To coordinatewiththe responsibledelivery ofopinionsin thePublic(c) To coordinatewiththe leadership, the agency/institutionwhich is the goalof deliveringthe opinion(d) Preparesecuringalocationand routethat passed.(e) responsibleforprotectingthe participantsinthe delivery ofpublicopinion(f) responsible fororganizingsecurityandfactorsfactors thatinfluence the implementation ofthe licensingpoliciesandnoticesof community activitiesare: (1) Communication; (2) Resources(3) Disposition; and(4) OrganizationalStructure.Keywords:Implementation ofLicensing PolicyandCommunityEventNotification.